Activities of St Casimir’s Society for Education and Care of Young People in Vilnius District (1925–1936) - Sereičikas , Mindaugas (Genocidas ir rezistencija, 2024)
On 8 October 1920, a group of Polish soldiers led by Gen. Lucjan Żeligowski, who officially became rebels, organised an anti-Lithuanian uprising and crossed the demarcation line provided for in the Suwałki Agreement and captured the city of Vilnius and its surroundings on 9 October 1920. Gen. Želigowski announced the creation of a new state, Central Lithuania (Pol. Litwa Środkowa), with Vilnius as its capital and himself as its leader. After the military offensive by Gen. Želigowski, which began during the occupation, Vilnius and the Vilnius region were isolated from Lithuania physically and culturally. Separated from Lithuania, the Lithuanians of Vilnius joined various organisations and societies to pursue national, cultural and political goals. One of the most massive organisations operating in Vilnius and Vilnius region during the occupation was the Lithuanian Society of St. Casimir for the education and care of young people.